ANALYSIS OF HALAL LITERACY LEVEL OF MSMEs in TASIKMALAYA - Nurhasanah, Elis; Az Zahra, Qiny Shonia (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2023)
The purpose of this study was to determine the level of halal literacy in food and beverage MSMEs, which includes halal literacy based on fiqh law, additives and critical points for non-halal food ingredients, and literacy in the halal certification process. Questionnaire using the Guttman scale. The results show that the level of halal literacy of MSMEs in Tasikmalaya is in the medium category. The literacy dimension regarding certification has the lowest score, namely 48 percent, or is in the low category, while the dimensions of halal knowledge in Islamic sharia (fiqh), additives, and the critical point of no-halal food ingredients are in the high category, at 93.9 percent and 84 percent, respectively. Thus, the mentoring process is needed by MSMEs to increase knowledge and help their products become halal certified.